On Certain Peculiarities of the Shock Wave Reflection - Walenta, Z.A. (Engineering Transactions, 1991)
The present paper discusses the results, both theoretical and experimental, in author's opinion most important for understanding the formation of a quasi-stationary reflection of a plane shock wave at a wedge. The peculiarities of the behaviour of the shock wave in close vicinity of the leading edge of the wedge are reported. The differences between the stationary shock reflection in the wind tunnel, and the quasi-stationary one in a shock tube, are specified. It is concluded that these two kinds of reflection can be equivalent only in the case of strong shocks.